Development of a Problem Based Learning Teaching Module on the Topic of Comparison to Facilitate Mathematical Reasoning Skills of Phase D Students - Putri, Aprilia Ihsani; Maimunah, Maimunah; Anggraini, Rini Dian (FKIP - Universitas Riau, 2025)
This research is motivated by the importance and low level of mathematical reasoning skills. The purpose of the research is to produce a Problem Based Learning-based teaching module on the topic of comparison to facilitate the mathematical reasoning skills of phase D students that meet the requirements of validity and practicality. The method used is Research & Development (R&D) with a 4-D development model (define, design, develop, disseminate). The test subjects were 6 eighth grade junior high school students in the small group test and 34 students in the field test. Based on the assessment by three validators, the teaching module met the valid criteria with an average percentage of 99% for part I of the teaching module, 94% for part II of the teaching module, and 97% for part III of the teaching module. The assessment of the student response questionnaire obtained an average of 91% with very practical criteria in the small group test and 96% with very practical criteria in the field test. It can be concluded that the Problem Based Learning-based teaching module on the topic of comparison to facilitate the mathematical reasoning skills of phase D students meets the valid and practical requirements.